CODESRIA Bulletin, No 1, 2023 - Journal System, (CODESRIA Bulletin, 2023)
In this Issue Editorial, Godwin R. Murunga ...................................................... 1 Editorial, Godwin R. Murunga ...................................................... 3 The Globalisation of Football is Closing Performance Gaps among Countries in the World Cup, Yusuf Bangura ......................................................... 5 African Feminist Epistemic Communities, Awino Okech ...........................................................13 Beyond Tinkering: Changing Africa’s Position in the Global Knowledge Production Ecosystem, Eyob Balcha Gebremariam, Isabella Aboderin, Divine Fuh & Puleng Segalo .......................................................19 Invisible Trillions: A Threat to Global Prosperity, Adeyemi Dipeolu...................................................25 Development, Development Cooperation and Africa in the Twenty-First Century, Grieve Chelwa ......................................27 Tribe and Tribalism in Kenya’s Politics, Peter Anyang’ Nyong’o & Caroline Karugu .................................33 Sierra Leone’s Voter Registration Data Discredits the Midterm Census Data: What are Implications for the Presidential Election of June 2023?, Yusuf Bangura ...............................................................36